Analyze the Influence of Corporate Social Responsibility on Human Resource Management - Yang, Shendi (Transactions on Economics, Business and Management Research, 2024)
The semiconductor sector in the United States is now experiencing a manpower shortage. To rectify this deficiency, Intel has instituted the RISE strategy as part of its corporate social responsibility (CSR) initiatives. The objective of this study is to examine how Intel amalgamates corporate social responsibility with human resource management to improve employee happiness. This research used qualitative approaches, utilizing Intel as a case study and integrating the Two-Factor Theory, Maslow's Hierarchy of Needs, and the CSR Pyramid Theory to examine the factors contributing to enhanced job satisfaction. The research culminates in the subsequent findings: Intel provides career development and planning services that serve as a motivating factor, facilitating continual employee growth. Companies should continue to expand their training material and improve their leadership training programs to fully recognize the developmental potential of their personnel. Secondly, Intel's dedication to employee health and welfare guarantees the satisfaction of fundamental and safety requirements. To achieve equilibrium between professional and personal life, organizations should augment their support for remote work. Ultimately, Intel has established a culture of diversity and inclusion, upheld ethical obligations and guaranteed equitable treatment for its employees. Organizations could augment employee happiness by enhancing openness in inclusive recruitment practices and standardizing procedures. This study offers empirical and theoretical evidence for the integration of CSR and human resource management  (HRM) to enhance employee happiness, serving as a reference for other firms to refine their HRM strategies and recruit prospective talent.